ANALISIS SEJARAH DAN PERKEMBANGAN TARI ZAPIN MELAYU - Putri, Areefa Zahira; Nofiani, Julia; Saputri, Arliani; Ardiansyah, Muhammad; Maryamah (Al Iman: Jurnal Keislaman dan Kemasyarakatan, 2025)
Zapin Melayu, a prominent traditional Malay dance, stands as a vibrant embodiment of Malay cultural heritage in Southeast Asia. This article offers a comprehensive exploration of Zapin Melayu, delving into its multifaceted dimensions. Originating from Arab influences, particularly the Hadhramaut region, Zapin Melayu has evolved into a distinct Malay artistic expression, characterized by its lively tempo, intricate footwork, and graceful hand movements. Accompanied by traditional musical instruments such as the gambus, marwas, gendang, and biola, Zapin Melayu performances are rich in rhythm and melody. Beyond its aesthetic appeal, this dance holds profound cultural and social significance for Malay communities. It functions as a crucial marker of Malay identity, reflecting historical connections, social values, and communal unity. This article examines the historical trajectory of Zapin Melayu, tracing its development and adaptation across different Malay regions. It analyzes the choreographic elements, musical structures, and symbolic meanings embedded within the dance, highlighting its role in social gatherings, ceremonies, and cultural celebrations. Furthermore, the article discusses the contemporary status of Zapin Melayu, addressing efforts towards its preservation and promotion in the face of modernization and globalization. Ultimately, this study underscores the enduring importance of Zapin Melayu as a living heritage, continually contributing to the richness and diversity of Malay culture and artistic traditions. Abstrak Zapin Melayu, sebuah tarian tradisional Melayu yang terkemuka, berdiri sebagai perwujudan dinamis dari warisan budaya Melayu di Asia Tenggara. Artikel ini menawarkan eksplorasi komprehensif tentang Zapin Melayu, menggali dimensi-dimensinya yang beragam. Berasal dari pengaruh Arab, khususnya wilayah Hadhramaut, Zapin Melayu telah berkembang menjadi ekspresi seni Melayu yang khas, dicirikan oleh temponya yang hidup, gerakan kaki yang rumit, dan gerakan tangan yang anggun. Diiringi oleh alat musik tradisional seperti gambus, marwas, gendang, dan biola, pertunjukan Zapin Melayu kaya akan ritme dan melodi. Lebih dari sekadar daya tarik estetikanya, tarian ini memiliki signifikansi budaya dan sosial yang mendalam bagi masyarakat Melayu. Ia berfungsi sebagai penanda penting identitas Melayu, mencerminkan koneksi historis, nilai-nilai sosial, dan persatuan komunal. Artikel ini mengkaji lintasan sejarah Zapin Melayu, menelusuri perkembangan dan adaptasinya di berbagai wilayah Melayu. Artikel ini menganalisis elemen koreografi, struktur musik, dan makna simbolis yang tertanam dalam tarian, menyoroti perannya dalam pertemuan sosial, upacara, dan perayaan budaya. Lebih jauh, artikel ini membahas status kontemporer Zapin Melayu, membahas upaya pelestarian dan promosinya dalam menghadapi modernisasi dan globalisasi. Pada akhirnya, studi ini menekankan pentingnya Zapin Melayu yang berkelanjutan sebagai warisan hidup, yang terus menerus berkontribusi pada kekayaan dan keragaman budaya dan tradisi seni Melayu.